(untitled) (REMUNOM, 2025)
Abstract Implant dentistry represented one of the greatest advances in rehabilitative dentistry, having established itself as a widely used functional and aesthetic alternative for the replacement of missing teeth. However, the presence of a history of periodontal disease in patients undergoing implant treatment raised important clinical concerns. Scientific evidence demonstrated that patients with periodontitis had a higher risk of developing peri-implant complications, such as mucositis and peri-implantitis, which compromised implant longevity and the health of peri-implant tissues. In this context, the importance of identifying associated risk factors, safer clinical protocols, and appropriate criteria for implant indication in patients with a periodontal history was recognized. This study aimed to evaluate the clinical viability of dental implant placement in individuals with a history of periodontitis, analyzing the necessary precautions, success rates, and the challenges involved. The research proposed a critical review of current scientific literature to support effective, safe, and personalized clinical approaches. The relevance of the investigation lay in the potential to improve evidence-based dental practice while positively impacting the quality of life of patients often marginalized in conventional oral rehabilitation indications. Thus, the study sought to contribute to a more humanized and scientific approach to managing these complex cases.